Synthetic aperture imaging of contact acoustic nonlinearity to visualize the closing interfaces using tone-burst ultrasonic waves. (15th June 2019) - Seo, Hogeon; Pyun, Do-Kyung; Jhang, Kyung-Young
Highlights: Synthetic Aperture Imaging of Acoustic Nonlinearity (SAIAN) is proposed. Contact acoustic nonlinearity is visualized by synthetic aperture focusing technique. A tone-burst wave is converted to a pulse-like contact acoustic nonlinearity signal. The SAIAN visualizes closing cracks, which is difficult by linear ultrasonic imaging. Probability of detection of a closing crack and accuracy in its sizing are increased. Abstract: Contact acoustic nonlinearity (CAN) effect was visualized by synthetic aperture focusing technique (SAFT) via a signal-processing method for acoustic nonlinearity imaging. The proposed signal-processing technique, named Synthetic Aperture Imaging of Acoustic Nonlinearity (SAIAN), allows the SAFT to visualize CAN that is difficult to be visualized by linear ultrasonic imaging. Using the SAIAN algorithm, the fundamental and second-order harmonic frequency components are extracted from the tone-burst wave signal and then these component signals are transformed into pulse-like signals. From the pulse-like signals, the CAN parameter signals can be obtained in the form of pulses, which allows CAN to be visualized by SAFT. In order to verify the effectiveness of the SAIAN, the nonlinear ultrasonic measurements using tone-burst waves were conducted to visualize closing interfaces. As a result, CAN effect appeared at partially closed part of a contacting interface in the images of the CAN signals converted by the SAIAN; on the contrary, the CAN feature was not shown in linear ultrasonic images based on the fundamental frequency component. These results support that the SAIAN is a useful signal processing for acoustic nonlinearity visualization that improves the probability of detection of closing interfaces and the accuracy in crack sizing.